Optimasi Kualitas Pelayanan dan Jasa: Tinjauan Implementasi Quality Function Deployment - Lilianti, Ananda; Safuan, Safuan (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The study investigates the implementation of Quality Function Deployment (QFD) in improving the quality of services in various service sectors. By analyzing 18 articles in national journals, the study identifies key factors that influence QFD implementation, such as employee training, infrastructure development, and customer satisfaction management. The results show that QFD is effective in improving customer satisfaction and optimizing service performance, with most common applications occurring in the transportation, banking, and health sectors. The implications of this research are the importance of continuous adaptation and innovation strategies in the face of competition in an increasingly competitive service market.